Enhancing Student Satisfaction with University’s Information in Social Media Environment: Mediating Role of Parasocial Interaction - Nam Hoai Nguyen; Phuc Thi Hong Nguyen; Ngoc Thi Pham (Economics Education Department Universitas Negeri Semarang, 2025)
Nowadays, universities use social networks as a crucial tool for providing information and engaging students. Factors like openness, perceived interaction, and parasocial interaction influence students' feelings toward these interactions. Parasocial interaction, the imagined relationship between the sender and receiver, significantly impacts students' attitudes and engagement. This study aims to evaluate the effects of perceived interaction, openness, and parasocial interaction on student satisfaction with university social networks. A survey of 346 students from universities in Hanoi, Vietnam, was conducted, and data were analyzed by the structural equation model (SEM). Results show that perceived interaction, openness, and parasocial interaction positively impact student satisfaction. Moreover, parasocial interaction mediates the relationship between perceived interaction, openness, and satisfaction. Additionally, content quality and responsiveness on social networks play a vital role in shaping students' perceptions and engagement. Universities that provide high-quality, timely content and meaningful interactions can strengthen student trust and satisfaction. These findings suggest that universities should optimize their social media strategies, focusing on interactive communication and content relevance to enhance student relationships and engagement.